PLEIJEL TYPE IDENTITIES - Aharonyan, N. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
In the present paper generalizations of classical Pleijel identities are obtained. We refer these identities as Pleijel type identities. Particular cases of these identities are proved in [1], [3] and [5].